Interactions between human granulocytes and Blastomyces dermatitidis. - Sixbey, J W (1979)
We studied interactions in vitro between human granulocytes and the yeast-like form of Blastomyces dermatitidis, because granulocytes are prominent in the host response to systemic blastomycosis. In Boyden chamber assays, broth culture filtrates of B. dermatitidis contained levels of granulocyte chemotactic activity that were significantly higher than those present in similar culture filtrates of Histoplasma capsulatum and Cryptococcus neoformans, two fungi that characteristically do not elicit granulocytes in infected tissues. Microscopic study, including electron microscopy, demonstrated that granulocytes phagocytosed B. dermatitidis promptly and efficiently. Moreover, granulocytes emitted light (chemiluminescence) at a brisk rate during phagocytosis of B. dermatitidis, indicating activation of intracellular metabolic pathways. However, fungicidal assay showed that granulocytes (1:1 cell-yeast ratio, 10% serum) killed only 29% of the B. dermatitidis inoculum during 3 h of incubation. Taken together, these findings suggest that there is disparity between phagocytosis and intracellular killing of B. dermatitidis by human granulocytes, perhaps because of resistance of this fungus to granulocyte microbicidal mechanisms.